PKM DIGITALIZATION OF BUSINESS PROFILES IN THE LEGAL FRAMEWORK OF EMPOWERING MSMES - Jasmalinda, Jasmalinda; Fauzia Zainin; Darlisma, Darlisma; mallisza, Danyl Mallisza (Journal of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, but most home-based micro MSMEs still face limitations in utilizing digital technology and understanding business legal aspects. This condition results in low competitiveness and weak business identities amidst the development of the digital economy. This Community Service activity aims to increase the capacity of MSMEs through training on digitalizing business profiles integrated with legal education as part of MSME empowerment efforts. The activity was carried out at the Madrasah Tarbiyah Islamiyah (MTI) in Indarung Village, Lubuk Kilangan District, Padang City, targeting home-based micro MSMEs, especially women. The implementation method included socialization, practical training on creating digital business profiles using mobile devices, mentoring, and discussions on the importance of business identity and legal protection in carrying out business activities. This activity was carried out collaboratively by involving academics from the Legal Studies Program of ITS Khatulistiwa, STIE Perdagangan Padang, and Ekasakti University. The results of the activity demonstrated improved understanding and skills among participants in developing more engaging and informative digital business profiles, as well as heightened legal awareness regarding the importance of legality and business identity. This activity is expected to serve as a model for sustainable collaborative service in supporting the strengthening of digital and legal-based MSMEs.